Pembelajaran Terbalik: Peningkatan Keterampilan Akuntansi Peserta Didik Melalui Model Pembelajaran Reciprocal Teaching - Ramadan Oktar Aswandi; Yuliana FH (Al-Mubin, 2025)
among vocational school students majoring in accounting. The research background highlights the dominance of conventional teaching methods that limit two-way interactions between educators and learners, causing low accounting proficiency. This study used a quantitative approach with a quasi-experimental design involving pre-test and post-test in a one-group setting. The research was conducted at SMK Bina Jaya Palembang involving 52 participants from class XI Akuntansi 2. The instrument used included essay-based accounting tests focused on inventory cards. The findings revealed a significant improvement in participants' accounting skills after the reciprocal teaching model was implemented. The average score increased from 49.01% (pre-test) to 72.71% (post-test), particularly in recording, analyzing, and presenting financial information. The conclusion suggests that reciprocal teaching effectively enhances learners' metacognitive engagement and critical thinking in accounting classes, supporting the Merdeka curriculum's emphasis on student autonomy